Computational engine performance and emission analysis using Ceiba pentandra biodiesel. Issue 3 (3rd May 2016) - Panneerselvam, N.; Murugesan, A.; Porkodi, K.P.; Jima, Terefe; Vijayakumar, C.; Subramaniam, D.
ABSTRACT: This paper investigates Ceiba pentandra methyl ester (CPME) as a renewable and alternative fuel source. It presents the results of performance and emissions characteristics of CPME blended with conventional diesel fuels in a diesel engine under full load conditions. The physicochemical properties of Ceiba pentandra oil were experimentally evaluated after transesterification and found to be within acceptable limits of relevant standards. It was clear that, when B25 tested in engine the BSFC increased by 6.2% and brake thermal efficiency reduced by 5.44% compared to diesel fuel. On the other hand carbon monoxide (CO) decreased by 8.33%, hydrocarbon (HC) reduced by 7.4% and oxides of nitrogen (NOx) also decreased by 3.72% compared to diesel. Smoke emissions of the biodiesel blend were 4.5% higher than diesel. Thus, B25 biodiesel blend can be used without any modification of the engine as an alternative and environmental friendly fuel.